2008
DOI: 10.1021/jo702617c
|View full text |Cite
|
Sign up to set email alerts
|

2-Position Base-Modified Analogues of Adenophostin A as High-Affinity Agonists of the d-myo-Inositol Trisphosphate Receptor:  In Vitro Evaluation and Molecular Modeling

Abstract: Adenophostin A (AdA) is a potent agonist of the D-myo-inositol 1,4,5-trisphosphate receptor (Ins(1,4,5)P 3 R). Various 2-aminopurine analogues of AdA were synthesized, all of which (guanophostin 5, 2,6-diaminopurinophostin 6, 2-aminopurinophostin 7, and chlorophostin 8) are more potent than 2-methoxy-N 6 -methyl AdA, the only benchmark of this class. The 2-amino-6-chloropurine nucleoside 11, from Vorbrüggen condensation of 2-amino-6-chloropurine with appropriately protected disaccharide, served as the advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The Adenophostins (A and B), products of Penicillium brevicompactum ,213 and their synthetic derivatives214 are the most potent IP3R agonists described to date. Adenophostin A has almost 100-fold greater affinity for IP3R than IP3215 and a mechanism has been proposed to account for this greater affinity 216,217.…”
Section: Pharmacological Tools For Investigating the Calcium Signalmentioning
confidence: 99%
“…The Adenophostins (A and B), products of Penicillium brevicompactum ,213 and their synthetic derivatives214 are the most potent IP3R agonists described to date. Adenophostin A has almost 100-fold greater affinity for IP3R than IP3215 and a mechanism has been proposed to account for this greater affinity 216,217.…”
Section: Pharmacological Tools For Investigating the Calcium Signalmentioning
confidence: 99%
“…Alternatively, the adenine of AdA may interact directly with the IP 3 R (Hotoda et al ., 1999; Glouchankova et al ., 2000; Rosenberg et al ., 2003). Such an interaction would need to be rather tolerant of changes to the adenine group because even substantial modifications to it cause only modest decreases in affinity (Correa et al ., 2001; Sureshan et al ., 2008). Defining the mechanisms responsible for high‐affinity binding of AdA would both provide an important step towards rational development of ligands of the IP 3 R with increased affinity, and contribute to resolving the mechanisms whereby IP 3 and AdA can have different effects on Ca 2+ signalling (Rossi et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1B). Despite considerable effort, fuelled by synthesis of many adenophostin A-related analogs (Borissow et al, 2005;Mochizuki et al, 2006;Sureshan et al, 2008), the structural basis of the high-affinity binding of adenophostin A to IP 3 R is unresolved. We have suggested that a cation-interaction between the adenine moiety of adenophostin A and Arg-504 within the IBC may contribute to this high-affinity binding (Sureshan et al, 2009).…”
mentioning
confidence: 99%